Tryptophan Degradation and Role NAD+ , SIRT1 of Ischemic Heart Diseases: Degradasi Triptofan dan Peran NAD+ , SIRT1 dalam Penyakit Jantung Iskemik - Kareema A. Dakhil; Zahraa Ali Nashoor Alnawas (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Ischemic heart disease (IHD) remains a major global health burden, primarily driven by atherosclerosis, thrombosis, and chronic inflammation. Specific Background: Emerging evidence implicates amino acid metabolism, particularly the tryptophan (Trp)–kynurenine pathway, in cardiovascular pathogenesis through its interplay with inflammation and energy homeostasis. Knowledge Gap: While the kynurenine pathway has been linked to cardiovascular disease, the specific role of Trp degradation in IHD, especially regarding NAD+ metabolism and SIRT1 regulation, is not well established. Aims: This study examined the association between Trp catabolism, NAD+ availability, SIRT1 expression, and inflammatory markers in IHD patients. Results: Compared with healthy controls, IHD patients exhibited significantly reduced serum Trp and NAD+ levels, while SIRT1 expression was markedly elevated. In parallel, inflammatory markers including CRP and Troponin were consistently higher across myocardial infarction, angina, and heart failure groups. Novelty: These findings highlight a distinct metabolic-inflammatory axis in IHD, where enhanced Trp degradation coincides with disrupted NAD+ homeostasis and compensatory SIRT1 elevation. Implications: Targeting Trp metabolism, NAD+ pathways, and SIRT1 regulation may offer novel diagnostic biomarkers and therapeutic strategies for IHD and related cardiovascular conditions.Highlight : Serum tryptophan and NAD+ levels are lower in IHD patients. SIRT1 levels are significantly higher compared to controls. CRP and troponin confirm inflammation and heart damage. Keywords : Ischemic Heart Disease, Tryptophan, NAD+, SIRT1, CRP, Troponin